Between Normality and Abnormality: Understanding the Social Support of People with Physical Disabilities Among Family - Kafaa, Kafa Abdallah (Universitas PGRI Madiun, 2024)
People with physical disabilities in Indonesia face a multitude of challenges, from physical barriers to social stigmas. This study examines the complexities of how people with physical disabilities navigate these challenges, focusing on the role of social support within families. The stigma of disability is often shaped by perceptions of